In-situ analysis of the lithium occurrence in the No.11 coal from the Antaibao mining district, Ningwu Coalfield, northern China - Sun, Beilei; Liu, Yunxia; Tajcmanová, Lucie; Liu, Chao; Wu, Jie (Ore geology reviews, 2022)
The occurrence of lithium (Li) in coal serves as the foundation for understanding the mechanism of its enrichment in coal and migration during combustion. However, owing to its low atomic weight, Li cannot be detected using conventional microbeam analyses, severely limiting its use. The high-Li Antaibao No.11 coal seam with a concentration of 99.1 μg/g Li was studied to determine the mode of occurrence and enrichment of Li. When compared to Chinese coal, the Antaibao No.11 coal is richer in SiO2, Al2O3, and TiO2. The carrier of Li was preliminarily determined using statistical correlation. In addition, two high-Li coal benches were subjected to in-situ analysis using time-of-flight secondary ion mass spectrometry (TOF-SIMS). The TOF-SIMS data show three types of Li occurrences in the first high-Li coal sample with a content of 179 μg/g. The main carriers of Li in this sample are illite, montmorillonite, chlorite, and tourmaline, according to the chemical maps for Li, Si, Al, Na, K, Ca, Mg, and Fe. This high-Li sample was formed by the interaction of two seawater-influenced coal seams. The interaction of fresh and saline waters makes the Li occurrence more variable. However, with a Li concentration of 260 μg/g in the second Li-enriched coal sample, Li only matches with Si and Al, indicating that Li is primarily found in kaolinite. This sample is formed between the parting and the seam with the greatest transgression. Boehmite is found in this sample in relation to the bauxite-bearing weathering crust. Locally, boehmite acts as a barrier to the infiltration and interaction of Li and other alkali and alkaline elements. As a result, Li is only associated with Si and Al. The terrigenous materials deposited within the original peat are responsible for the enrichment of Li in this sample.
Gesehen am 06.07.2022